Winning CFOs : implementing and applying better practices - Parmenter, David (Hoboken, N.J. : John Wiley & Sons, 2011)
'Better practices today's CFOs can employ to bring value and efficiency to the teams that report to them Helping financial managers implement better practices that will make a difference to their finance team's performance, Winning CFOs shows financial managers how to create permanent improvements in their organization's processes. Provides better practice solutions the author has learned from more than 4,000 financial managers worldwide A to Z on how to be an effective CFO Includes templates, checklists and implementation programs that will have a significant impact on how financial managers improve their processes Abundance of tools to ensure your implementation of better practices has a flying start. Tips on how to develop winning leadership traits Winning CFOs shows senior financial managers how to radically transform their contribution to their organisation, enhance their job satisfaction and profile, and leave a legacy of efficiency and effectiveness in every organization for which they work.'--
Includes index.
Keywords: Chief financial officers; Organizational change; Leadership